The quality debates in international higher education on competition for students from an european perspective - Ortega-Mohedano, José; Rodríguez-Conde, Mª José (11th Annual International Conference of Education, Research and Innovation (ICERI), 2021)
Higher education is facing, worldwide, a context of greater competition for students. It is a new environment of competition for the student, based both on reasons of supply (offer available to the student), and demand (students demanding educational services) in the field of higher education. Of supply, due to reasons like the growing liberalization of the sector, the integration of higher education systems, the expanding institutional mobility beyond borders, or a greater visibility of the university offer thanks to the internet. And of demand, due to the mobility policies of teachers and students promoted by the governments, the higher level of foreign language learning by students, or the need to build an international curriculum; among others. As a result, the university, and in particular the European public university, faces a situation of loss of its privileged status, in terms of its positioning in the market of higher education. Indeed, today it is rather just the international recognition of studies -in terms of accreditation or approval- that prevents a student, and only to some extent, to decide either to study here or there, this way or another. That is, the future higher education student runs into a global mobility as a result of the increasing reduction of barriers to entry and exit from the higher education sector. Greater mobility that is physical, but also "virtual", thanks to the new information and communications technologies. This requires universities, necessarily, to develop strategies for the student competition. Therefore, it would be worth considering, if it was justified to prioritize the quality of universities from the European Higher Education Area (EHEA) as a competitive strategy. To answer, in this study we assess the magnitude and characteristics of student's mobility in the world, particularly in the EHEA. We ask ourselves, what leads a foreign student to choose to learn on a country or another. More specifically, on a university or another. The European Union (EU), aware of the need for a competitive university, has opted for quality to reinforce its international appeal. To do this, it urges to recognize excellence and encourages competition in the higher education sector. However, an approach to quality in higher education institutions (HEIs), represents a radical change of strategy, which has opened several debates, both in Spain and at the EU level. In this paper we have analyzed three: "homogeneity vs. diversity" of university models; the controversy of the "university rankings" within a discussion about the comparative criteria between different models of higher education; and the applicability of total quality management (TQM) in the field of higher education. Overall, this is a triple level of discussion about planning, assessment and management of higher educational systems of quality within the EHEA, which in this study was examined particularly from the paradigm of market orientation, namely oriented on the student.
Ponencia del congreso: 11th Annual International Conference of Education, Research and Innovation (ICERI)
Keywords: internationalization; international education; ehea; higher education; quality; quality in higher education; student orientation; WOS(2)